Immune checkpoint inhibitor‐related adverse events in lung cancer: Real‐world incidence and management practices of 1905 patients in China. Issue 3 (21st December 2021) - Shi, Yuequan; Fang, Jian; Zhou, Chengzhi; Liu, Anwen; Wang, Yan; Meng, Qingwei; Ding, Cuimin; Ai, Bin; Gu, Yangchun; Yao, Yu; Sun, Hong; Guo, Hui; et al.
Abstract: Background: Immune checkpoint inhibitors (ICIs) are the standard treatment for advanced lung cancer, but immune‐related adverse events (irAEs) remain poorly understood, especially in a real‐world setting. Methods: A multicenter observational study was conducted. Medical records of lung cancer patients treated with ICIs at 26 hospitals from January 1, 2015, to February 28, 2021, were retrieved. Types of ICIs included antiprogrammed cell death 1 or antiprogrammed cell death ligand 1 (PD‐L1) monotherapy, anticytotoxic T‐lymphocyte antigen‐4 monotherapy, or combination therapy. Results: In total, 1905 patients with advanced lung cancer were evaluated. The median age was 63 (range 28–87) years, and the male/female ratio was 3.1:1 (1442/463). The primary histological subtype was adenocarcinoma (915). A total of 26.9% (512/1905) of the patients developed 671 irAEs, and 5.8% (110/1905) developed 120 grade 3–5 irAEs. Median duration from ICI initiation to irAEs onset was 56 (range 0–1160) days. The most common irAEs were thyroid dysfunction (7.2%, 138/1905), pneumonitis (6.5%, 124/1905), and dermatological toxicities (6.0%, 115/1905). A total of 162 irAEs were treated with steroids and 11 irAEs led to death. Patients with positive PD‐L1 expression (≥1%) and who received first‐line ICI treatment developed more irAEs. Patients who developed irAEs had a better disease control rate (DCR, 71.3% [365/512] vs. 56.0% [780/1145]; p < 0.001). Conclusions: The incidence rate of irAEs was 26.9% in a real‐world setting. IrAEs might be related to a better DCR, but clinicians should be more aware of irAE recognition and management in clinical practice. Abstract : This was a multicenter observational study of real‐world treatment status immune checkpoint inhibitors (ICIs) and incidence of immune‐related adverse events (irAEs). A total of 512 (26.9%) of 1905 patients developed 671 any grade irAEs and 110 (5.8%) patients developed 120 grades 3–5 irAEs. Positive programmed cell death‐ligand 1 expression, first‐line ICI treatment and sustained disease control were observed more in patients with irAEs.